Sistem Pengingat Safety Riding bagi Pengemudi Mobil Pribadi - Hugeng Hugeng; Eko Syamsudin; Hadytio Putra (Ultima Computing : Jurnal Sistem Komputer, 2014)
The purpose of the utility of safety belt is to minimize the impact that could occur in a car accident. Safety belt consists of two main parts; i.e. transverse diagonal sash belt and lap belt that lies horizontally on the abdomen. Both parts make a form of continuous network that securing the driver. The main problem in the usage of safety belt is that many drivers ignored the function of the safety belt and did not use it. Some drivers tightened one part of the belt only, others even did not use it at all. Facing this problem, a model was designed in this research that can always remind and force the drivers to use their safety belt. Additional features were detection system for car speed and for driver’s head position. This designed device consists of several main components such as microcontrollers, limit switches, heat sensors, sound system, an accelerometer, and potentiometers. Some components were designed based on separate modules and merged into a single unit device that can always remind drivers to use safety belts correctly. Based on the results of the conducted experiments, the system can function correctly in which it always perfomed rechecking of each parameter. Index Terms - microcontroller, safety riding system